Spontaneous Parametric Down-Conversion Beaming from a Lithium Niobate Nanostructured Resonator - Zilli, Attilio; Sultanov, Vitaliy; Poloczek, Michael; Ferrera, Marzia; Luan, Yigong; Kokkinakis, Emmanouil T.; Santiago-Cruz, Tomás; Carletti, Luca; Toma, Andrea; Finazzi, Marco; Chekhova, Maria V.; Celebrano, Michele (2023 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2023, 2023)
Lithium niobate (LiNbO3) is a prime material for photonics thanks to a unique mix of properties, including strong electro-optical and nonlinear optical responses as well as a broad transparency window spanning the visible and near-infrared (NIR) range (0.35 to 4.5 μm). Despite the inherent challenges in the nanofabrication of LiNbO3, caused by its hardness and resistance to chemical etching, recent technical advances eventually enabled the realization of deeply sub-μm features in LiNbO3, thereby enabling a series of breakthroughs in the field of nano- and meta-photonics [1]. Nonlinear nano-optics has especially benefitted from such improvements thanks to the large second-order diagonal nonlinearity of LiNbO3. Several LiNbO3 metasurfaces have been designed to enhance and steer second-harmonic generation (SHG) [1] emitted up to the visible range [2]. Similar designs were also exploited for generating photon pairs via spontaneous parametric down-conversion (SPDC) [3], a quantum process where a single photon is converted into two photons of the same total energy, see Fig. 1c (right).
CRIS-Team Scopus Importer:2023-11-17